Building lecturers bagged Silver Medal in IID 2018 / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A team of innovative lecturers led by Muham-mad Naim Mahyuddin assisted by colleagues, Dr. Dzulkarnaen Ismail, Sr. Anas Zafirol Abdullah Halim, Mohamad Hamdan Othman and Mohd Najib Abdul Rashid bagged a Silver Medal in the recent Invention, Innovation and Design Competition (IID) 2018. The competition was held digitally on August 28, 2018.